2008
DOI: 10.1159/000112840
|View full text |Cite
|
Sign up to set email alerts
|

Axillary and Rectal Temperature Measurements Poorly Agree in Newborn Infants

Abstract: Aim: Evaluation of the agreement between axillary temperature measurements and rectal temperature measurements in neonates. Methods: Rectal and axillary body temperatures were simultaneously measured for 3 min in 33 neonates (gestational age 25–42 weeks, weight 840–4,005 g). Two investigators performed paired measurements, one in each neonate. A single type of thermometer was used in this study: one thermometer for each rectal and another thermometer for each axillary measurement. The Bland-Altman method was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 43 publications
0
15
3
Order By: Relevance
“…In the study of Friedrichs et al [10], temperature obtained from the left axilla had higher correlation with rectal measurements as compared to that of the right axilla. Our results also contradict those of Hissink et al [6], Hutton et al [7], and Lee et al [9]. Comparing the agreement between axillary and rectal thermometry using the Bland-Altman method, all above studies reported significant differences in healthy and sick term and preterm neonates (range: 25–42 weeks gestation), including those in NICU settings.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the study of Friedrichs et al [10], temperature obtained from the left axilla had higher correlation with rectal measurements as compared to that of the right axilla. Our results also contradict those of Hissink et al [6], Hutton et al [7], and Lee et al [9]. Comparing the agreement between axillary and rectal thermometry using the Bland-Altman method, all above studies reported significant differences in healthy and sick term and preterm neonates (range: 25–42 weeks gestation), including those in NICU settings.…”
Section: Discussioncontrasting
confidence: 98%
“…Comparing the agreement between axillary and rectal thermometry using the Bland-Altman method, all above studies reported significant differences in healthy and sick term and preterm neonates (range: 25–42 weeks gestation), including those in NICU settings. Moreover, Hissink et al found that axillary temperature was lower than rectal ones, and that increasing postnatal age increased the difference between the two measurements [6]. …”
Section: Discussionmentioning
confidence: 99%
“…In the neonates, however, the findings are not uniform. While this present study and some other studies510 have found significant mean differences between the rectal and axillary temperatures in neonates, another11 found no significant difference. This raises another question as to whether the axillary route is accurate enough to be used as a surrogate to rectal thermometry in neonates in whom rectal thermometry is avoided because of accidents like perforations 12…”
Section: Discussioncontrasting
confidence: 80%
“…and Muller et al. (11,12)found poor agreement between axillary and rectal temperatures. A systematic review of nine studies comparing axillary vs. rectal showed mean difference of 0.17°C with the limits of agreement of 0.15–0.5 °C, which may be acceptable in normothermic babies (9).…”
Section: Descriptive Statisticsmentioning
confidence: 94%